User Privacy Preservation in AI-Powered Digital Communication Systems - Gemiharto, Ilham; Masrina, Dwi (Jurnal Communio : Jurnal Jurusan Ilmu Komunikasi, 2024)
In an era dominated by AI-powered digital communication systems, concerns about user privacy have taken center stage. This research aims to understand and assess the strategies employed to preserve user privacy in such a system. Specifically, it seeks to identify the range of privacy preservation methods, evaluate the transparency of data collection and usage, and analyze the mechanisms for obtaining user consent. Additionally, the research aims to assess the impact of these strategies on user trust and satisfaction. This research presents a comparative case study to achieve these objectives. A qualitative comparative case study methodology focused on multiple AI-powered digital communication systems, comparing different privacy preservation strategies across various platforms. Data was collected through in-depth interviews with system developers and users, content analysis of privacy policies, and user experience assessments. The in-depth interviews provided insights into the practical challenges and strategies from the perspective of both developers and users. In contrast, the content analysis and user assessments offered a comprehensive understanding of the implemented privacy measures and their perceived effectiveness. The findings reveal diverse approaches to user privacy preservation, ranging from end-to-end encryption to data anonymization. Variations were observed in the transparency of data collection and usage and the mechanisms for user consent. The study also highlighted the impact of these strategies on user trust and satisfaction. This research underscores the importance of a nuanced approach to user privacy preservation, considering both technical and ethical dimensions. It emphasizes the need for transparent communication between users and system developers and the role of legal frameworks and industry standards in shaping privacy practices. In the context of AI-powered digital communication systems, this comparative case study sheds light on the multifaceted landscape of user privacy preservation. It advocates for a holistic approach that combines technical safeguards, ethical considerations, and regulatory measures to ensure user privacy in an increasingly interconnected digital world.